Case report: Giant meningioma of the left hemisphere - Cui, Junxiang; Sun, Hu; Sun, Shuo; Zhao, Hao; Gu, Yinghao (Frontiers in Oncology, 2024)
Meningiomas are some of the most prevalent primary brain tumors in adults, and are typically non-neuroglial in nature. A variety of symptoms may be observed, including headaches, fluctuations in mental status, ataxia, muscle weakness, nausea and vomiting, seizures, visual changes, speech disorders, and sensory abnormalities. The World Health Organization (WHO) has a grading system for meningiomas based on histological criteria, which is as follows: Grade 1 meningiomas are considered benign; Grade 2 meningiomas have a moderately aggressive nature and usually present with histological atypia; and Grade 3 meningiomas exhibit aggressive malignant behavior. Grade 3 meningiomas are distinguished by aberrant and accelerated cellular proliferation, which increases the probability of invasion and recurrence within the central nervous system relative to the other grades. Malignant meningiomas are further classified by tumor size. For example, WHO grade 3 meningiomas with diameter >5 cm are designated giant meningiomas. Giant meningiomas are complicated by their potential for compression of the brain tissue, which can lead to increased intracranial pressure and hemodynamic changes. In many cases, these changes induce vasogenic edema in the adjacent brain tissue. This article details a rare case of rapidly growing atypical giant meningioma that progressed to an anterior-posterior diameter of 13 cm within 3 years, occupying the majority of the left hemisphere of the brain and encroaching upon the right intracranial structures. Through recent advances in medical diagnostics and heightened public awareness of health issues, cases with such large meningiomas have become exceedingly rare. Fortunately, the tumor in the present case was successfully resected using advanced surgical techniques that employed microscopy in conjunction with sodium fluorescein, resulting in complete removal of the tumor and restoration of the patient’s muscle strength postoperatively. The value of fluorescence-guided surgery in this type of procedure is support in the present case report.